Effect of Clinical Sandblasting on the Surface Roughness of Zirconia Cores for all Ceramic Crowns and their Fracture Resistance after the Addition of Repair. - Mohammed Thamir Yassin; Shatha Abdullah Salih (Erbil Dental Journal)
Objective: This in vitro study aims to evaluate the effect of clinical sandblasting with 50 μm aluminum oxide and 30 μm silica-coated particles on the surface roughness of zirconia cores and the subsequent effect on their fracture resistance after veneering with composite using a specific repair kit. Materials and Methods: Zirconia cores (n=21) were digitally designed and milled from ZirCAD LT B1 (IPS e.max® ZirCAD ) blocks using arum 5x-300 Pro (ARUM DENTISTRY). These cores were randomly divided into three groups: Group A: n=8, sandblasted with 50 μm aluminum oxide, and veneered with packable Z350 composite. Group B: n=8, sandblasted with 30 μm silicacoated particles and veneered with packable Z350 composite. Group C: control group (n=5), sandblasted in the laboratory with 110 μm aluminum oxide and veneered with porcelain (Vintage Zr PRO - SHOFU Dental GmbH). All the specimens were tested for surface roughness by the TAYLOR-HOBSON profilometer. After adding veneering material, all the specimens were subjected to a fracture resistance test through a universal testing machine. Results: One-way ANOVA test showed a significantly higher surface roughness in group B compared to group A. Fracture resistance values showed no significant difference between all the groups. Conclusion: Silica-coated particles produced higher surface roughness than aluminum oxide alone. The fracture resistance values of all the groups were above the acceptable clinical limit.